Extraction of dibenzothiophene from model oil using ionic liquids - Kenrick, Bilong Pius (2014)
Diesel fuel in contrast has many benefits in our daily lives, which is use to power up vehicles and heavy machineries. Besides that, from the usage of diesel, it will produce sulfur when combustion is involved. Currently, Malaysia is making its effort to reach the sulfur target of 50 ppm as implemented by the Euro IV standards. Sulfur is very harmful towards humans, animals, machines and the environment. Sulfur contributes to air pollution by creating acid rains; in conjunction to machineries, it will corrode the equipment from the inside and thus reducing its effectiveness and requires a high cost to repair and maintenance. In this research, a sulfur compound called dibenzothiophene (DBT) is chosen as the study case. The objective of this research is to determine whether dibenzothiophene (DBT) can be extract or remove from model oil of n-hexane using an ionic liquid. The ionic liquid that is to be used is 1-methylpyrazolium ethyl sulphate C6H13N2O4S. The ionic liquid is to be tested on a model oil of n-hexane to check its sulfur removal efficiency. A Fourier Transform Infrared Spectroscopy (FTIR) is conducted on the ionic liquid to check its content and an Infra-Red (IR) absorptions classification according to the wavelength is obtained to determine their functional groups. Next, the ionic liquid is tested on a Carbon Hydrogen Nitrogen and Sulfur (CHNS) analysis, to check its sulfur content. From the CHNS analysis, a manual calculation is to be done to check the molecular formula and compare it with the existing molecular formula, C6H13N2O4S. On top of that, a High Performance Liquid Chromatography (HPLC) analysis is conducted. A series of concentration for standard sample and sample is prepared. The samples consist of concentration in the range of 1500ppm to 250ppm. For the standard sample, the model oil of n-hexane is mixed with dibenzothiophene (DBT) is analyse and a calibration curve is plotted. For the sample, the ionic liquid is mixed with the model oil and dibenzothiophene (DBT) is analyse. From the data obtained it is then compared with the calibration curve and the sulfur removal efficiency is calculated. A bar chart for each of the concentration was plotted. From the result, it was found out that the sulfur removal is highly efficient at concentration of 1500ppm with 90.98%. In return of this work, perhaps a further research on diesel using ionic liquid will be conducted